Haematological Responses following Oestrus synchronisation and superovulation protocols in West African Dwarf Goats - Adah, Adakole (Universitas Airlangga, 2023)
Experiments were performed to evaluate the haematological (erythrocyte and leucocyte parameters) response of West African Dwarf goats following oestrus synchronisation and superovulation protocol. Twenty-four clinically healthy female goats aged 2.34 ± 0.4 years and average body weight of 13.83 ± 0.7 kg was used for the experiment. The goats were divided into two groups. Group I goats was synchronized using Controlled Internal Drug Release (CIDR) for 18 days with the first day of insertion as day 0. On day 16 following CIDR insertion into the vagina, a single dose of 500 IU equine chorionic gonadotropin (eCG) was administered to each doe intramuscularly while group II served as the control was subjected to the same housing and environmental conditions but was not synchronized. superovulation was induced with porcine follicle stimulating hormone (pFSH) which was injected intramuscularly at a rate of 5mg/kg in reducing doses twice a day at 06.00 h and 18.00 h for 3 days starting from 48hr i.e., 2 days before CIDR removal (day 17). A blood sample of 5 mL was collected by jugular venipuncture of each of the goats before the protocol (Day 0) and at the end of the protocol (Day 18). All erythrocyte parameters evaluated showed a significantly higher value in group II (control) compared to group I post-oestrus synchronisation while total leucocyte count, neutrophil count and neutrophil/lymphocyte ratio values obtained after the protocol were also higher in group I (P < 0.05) compared to group II. It is therefore concluded that oestrus synchronisation and superovulation may elicit stress in West African Dwarf goats and an appropriate antioxidant should be part of the protocol.